Educating future managers on how to help motivate employees to follow food safety practices. - Roberts, Kevin R.; Arendt, Susan W.; Strohbehn, Catherine; Ellis, Jason D.; Paez, Paola (My University, 2014)
Current and future foodservice managers’ perceptions about motivating employees to practice safe food handling were examined as a basis for developing recommendations to improve dietetics and hospitality educators’ pedagogy related to employee motivation. Perceptions about teaching and delivery methods also were explored. Four focus groups were conducted in Iowa and Kansas; two with future managers (students) and two with current managers. Five major themes emerged from the qualitative data analysis: communication, customization, operations, training methods/materials, and human resources. Each motivator is discussed and suggestions are provided for enhancing teaching and learning in foodservice management programs.
Keywords: Food safety; Foodservice; Education; Managers; Motivation; Teaching and training methods